Rural population and medical care in the Płock government In the second half of the XIX and in the beginning of the XX century - Milewska, Marta (Marginesy, 2021)
The political situation, the developing capitalism and conditions of the natural environment had a significant impact on the state of medical care in the Płock governorate in the second half of the 19th century and at the beginning of the 20th century. The article presents a system of medical care modeled on terrestrial medicine, introduced as a trial in 1899 in the Płock governorate. This system was to provide the rural population with access to free medical assistance to become a model for other governorates. Unfortunately, its shortcomings decided about the failure of the entire undertaking. The purpose of the article is also to present the situation of the rural population, their difficulties in accessing medical advice and hospitals, and the related consequences affecting the development of witchcraft.